2020
DOI: 10.1111/jam.14576
|View full text |Cite
|
Sign up to set email alerts
|

An improved cleaning system to reduce microbial contamination of poultry transport crates in the United Kingdom

Abstract: Aim Following previous research on improving the cleaning of crates used to transport broiler chickens from the farm to the abattoir, a demonstration project was undertaken to investigate improvements in crate washing on a commercial scale. Methods and Results The soak tank of a conventional crate washing system was replaced with a high‐performance washer fitted with high‐volume, high‐pressure nozzles. The wash water could be heated, and a greatly improved filtration system ensured that the nozzles did not los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…Insufficiently cleaned transport crates is another risk factor for chickens becoming colonized with Campylobacter especially during thinning, when birds in a flock are sent to slaughter in separate batches on two or more slaughter occasions [18,24,25]. In this study, 30% of transport crates dispatched by the slaughterhouse were contaminated with Campylobacter already on arrival at farm level before loading up the chickens to send to slaughter.…”
Section: Discussionmentioning
confidence: 78%
“…Insufficiently cleaned transport crates is another risk factor for chickens becoming colonized with Campylobacter especially during thinning, when birds in a flock are sent to slaughter in separate batches on two or more slaughter occasions [18,24,25]. In this study, 30% of transport crates dispatched by the slaughterhouse were contaminated with Campylobacter already on arrival at farm level before loading up the chickens to send to slaughter.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, no correlation was observed between the AIV genome detection results and results of cleanliness inspection and microbiological counts. Regarding visual inspection, it is common to observe uncorrelated results between cleanliness and microbiological counts ( Allen et al, 2008 ; Atterbury et al, 2020 ). Visual inspection is a prerequisite before microbiological testing; the latter should be performed on visually clean surfaces only.…”
Section: Discussionmentioning
confidence: 99%
“…This makes them potential vehicles for transmission of Campylobacter between broiler flocks in conjunction with thinning ( Slader et al, 2002 ; Hansson et al, 2005 ). There is also evidence that current commercial washing systems for crates do not reduce microbial contaminants such as Campylobacter ( Slader et al, 2002 ; Atterbury et al, 2020 ). Hence there are risks of bacterial spread ( Allen et al, 2008b ; Frosth et al, 2020 ; Hertogs et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that pathogenic bacteria, such as Campylobacter spp. and Salmonella spp., remain present on transport crates for chickens even after cleaning and disinfection ( Hansson et al, 2005 ; Atterbury et al, 2020 ). However, in applied research indicator bacteria are often used instead of pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation